GEOGRAPHICAL CONTEXT AND NATURAL ENVIRONMENT PRESERVATION IN LOCAL CULTURE (A study on the Ritual of Penti in Manggarai, Flores NTT) - Erna Mena Niman (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Indonesia has a great number of local cultures. Such local cultures exist along with the values, norms, and thought of the society. One of the local culture in question is Penti ceremony that is conducted anually by Manggaraian people in the west of Flores. This study was an attempt to reveal the the geographical context found in the ritual of penti ceremony. To gather the data, interview and observation were carried out and were analyzed in some stages namely data reduction, data display and verfication. The results have shown that the geographical context in the penti covers both natural spatial and social aspects. The natural spatial aspect is concerned with the selection of the locations where the the ritual of penti is carried out. The selected locations were regarded as media for communication and.were as reflections of interpersonal relations and the cosmological view of the Manggarain community towards nature. Meanwhile, the social aspect regulates the social relations of the community which is manifested in the form of norms, ethics, and prohibitions. As a conclusion, the geographical context in the ritual of penti is closely related to natural environment preservation and social life sustainbility. Keywords: penti; spatial and social geography